Exploring Protective and Risk Factors Among Youth in High-risk Areas - Amin Al Haadi Shafie; Dini Farhana Baharudin; Khatijah Othman; Ahmad Najaa' Mokhtar; Nur Fatini Kamal; Abdul Rashid Abdul Aziz; Suzaily Wahab; Anita Priantina; Nurhafizah Yassin; Mohd Azwan Fakhruddin Abd Halim (Kuey, 2024)
Non-Indexed Publication